NORMALIZATION OF DIFFICULT LOAN PAYMENTS: A SEMIOTIC ANALYSIS OF LOAN SERVICE ADVERTISEMENT IN POST PANDEMIC ERA - Fani Indrawan; Nimas Diah Putri Ayu Dewi Nastiti (Teaching English as Foreign Language, Literature and Linguistics, 2022)
This study focuses on semiotic analysis of Kredivo's commercial video entitled "Life as flexible as it can beâ€. The purpose of this research is to find the hidden meaning behind the sign used in the commercial. This study uses a descriptive qualitative approach to seek a deeper understanding of the meaning contained in the commercial. The theory used in this study is the semiotic analysis of Roland Barthes. The results of this study indicate that there are some hidden meanings that are made vague by only showing certain messages in a clear and straightforward manner so that the purpose of this Kredivo commercial is achieved. However, the hidden meaning can still be revealed and stated in the results of this study. The conclusion of this study is that Kredivo uses the slogan "Flexible" to build image that its users have the freedom to use their loan services. In addition, through this commercial, Kredivo also wants to instill an understanding that the comforts and difficulties in life are normal. To normalize the difficulty faced by its users after taking their loan service. As it can be normal, users do not need to worry and exaggerate it.